Relevant Market and Pricing Behavior of Regional Newspapers in the Netherlands - Hans L. van Kranenburg (Vierteljahrshefte zur Wirtschaftsforschung, 2005)
Ziel der vorliegenden Untersuchung ist es, den Einfluss von Marktstruktur und anderen regionalen Einflussgrößen auf die Preise der Zeitungen für Abonnements und Anzeigen zu analysieren. Im Ergebnis zeigt sich insbesondere eine negative Korrelation von Konzentration und Zeitungspreisen. Die Preise für Anzeigen hängen - anders als die für Abonnements - signifikant vom Einkommensniveau und der Bevölkerungsdichte in der jeweiligen Region ab. Weiterhin deutet die empirische Evidenz darauf hin, dass zu den relevanten Märkten für Regionalzeitungen in den Niederlanden auch die überregionalen Zeitungen und andere Medien gehören. – – The aim of this study is to investigate the effect of market structure and area characteristics on the subscription prices and advertising rates for regional newspapers in the Netherlands. The price-market structure analysis in this study shows that there exists a negative relationship between concentration and prices. The results also show that advertising rates, differently to subscription prices, are significantly influenced by regional income and particularly by population density in the specific area. Furthermore, the evidence indicates that the relevant market for regional newspapers in the Netherlands is a market which encompasses regional newspapers, national newspapers and other media sources.
Keywords: 330; Zeitung; Printwerbung; Preis; Marktstruktur; Regionale Preisstruktur; Presseverlag; Regionales Cluster; Schätzung; Niederlande